Artificial neural networks for hybrid inertial-satellite navigation systems: challenges, tasks and recent research - Lashchenko, O. L. (National Technical University "Kharkiv Polytechnic Institute", 2025)
This paper addresses the problem of unreliable or falsified GNSS signals and presents advanced methodologies for their detection. The focus has been made on the integration of machine learning techniques, particularly Artificial Neural Networks (ANNs) into hybrid navigation systems to model temporal and spatial anomalies in GNSS data, enabling the system to distinguish between authentic and corrupted signals.
Keywords: GNSS; inertial navigation; artificial neural networks